Nursing care to the patient victim of traumatic brain injury (Research, Society and Development, 2022)
Introduction: the Traumatic Brain Injury (TBI) is an injury resulting from an external trauma, which results in anatomical changes of the skull, such as fracture or laceration of the scalp, as well as functional impairment of the meninges, brain or its vessels, resulting in temporary or permanent alterations, of a cognitive or functional nature. Objective: the interest of this work arose from the concern to demonstrate the importance of nurses in caring for patients with traumatic brain injury, since, through proper care and identification of signs for an early diagnosis, it can reduce the aggravation of existing injuries and avoid possible complications. Materials and methods: the bibliographic research is developed from material already prepared, consisting of scientific articles and whose research is carried out through the technique of content analysis. Results and discussion: it was possible to verify how much this professional performs essential activities as a member of the health team. In handling the patient who is a victim of TBI, the nurse makes use of protocols that guarantee a quick assessment, readiness at the beginning of interventions and stabilization of the victim's respiratory, ventilatory and hemodynamic conditions, allowing the nurse and the team to spend less time for care, efficiency, less possibility of errors and greater effectiveness in the assistance provided. Final considerations: it was possible to identify the importance of the nurse's role in caring for patients with traumatic brain injury, since they maintain direct contact with the patient present there and perform their care throughout their stay in the service.